Transforming Indonesian Literature Learning through Virtual Reality and Augmented Reality - Septiaji, Aji; Nurhidayat, Eka; Miftahudin, Iip; Choerunnisa, Nanis Regina (Proceeding International Conference on Education, 2025)
The development of digital technology has opened new opportunities in developing literary learning models, particularly through the utilization of Virtual Reality (VR) and Augmented Reality (AR). This study aims to examine the transformation of Indonesian literature learning through the integration of VR and AR technologies. Using a qualitative approach and library research methods, this study analyzes various literature sources that discuss technology-based learning innovations and their implications for improving literary literacy. The study results indicate that virtual reality technology allows students to "enter" the world of literary texts, such as exploring story settings or interacting with characters visually and sensorily, thereby strengthening imagination and contextual understanding. Meanwhile, augmented reality can be used to enrich printed texts with digital elements such as animations, videos, or audio narratives that appear through device scanning, thereby increasing students' reading interest and engagement. This transformation brings about a paradigm shift in literature teaching from conventional narrative-based approaches to multimodal approaches that have emotional and cognitive impacts. These findings confirm that VR and AR not only enhance interactivity in literary learning but also open new spaces for developing creativity, empathy, and aesthetic appreciation of Indonesian literary works among students. This study recommends curriculum development and educator training to optimize the use of impactful technology in literature learning in the digital age.